Բաթումի պայմանագիրը և Հայկական հարցը - Էդգար Նավոյան (ՀՀ ԳԱԱ հրատ.)
Батумское соглашение является логическим продолжением Брестского мирного договора. К счастью, это соглашение имело короткую жизнь. Мудросское перемирие дало Армении возможность вернуть Карс и Ардаган и вновь поднять Армянский вопрос на международной арене. Treaty of Batum is the logical continuation of the Brest-Litovsk peace treaty. This treaty was fortunately soon terminated. The defeat of the Ottoman Empire in the First World War and the armistice of Mudros gave Armenians an opportunity to suspend the treaty of Batum, that they were forced to sign, to recapture Ghars, Ardahan, Surmali and to raise once more the Armenian Question in the international arena.
Keywords: Armenian Question; Modern History; Political Science